Postpartum Depression in Women with Normal Delivery and Cesarean Section Referring to Sayad Shirazi Hospital of Gorgan , Iran - Mohammad-Zaman Kamkar; Ali balajalini; Fatemeh Zargarani; Naser Behnampour (Golestan University of Medical Sciences, 2019)
Background and objectives: During the postpartum period, mothers may experience physical and emotional changes. Postpartum Depression (PPD) may affect 10-15% of all women after delivery. In some studies, the type of delivery has been considered as a risk factor for postpartum depression. The present study was designed to investigate and compare the frequency of postpartum depression in women with normal and cesarean delivery. Methods: This descriptive-analytic study was conducted on 300 women referring to the Sayad Shirazi Hospital. First the Women who had Beck depression inventory score>12 were excluded and then the participants were divided into two equal groups of normal (150) and cesarean (150) delivery. Two weeks after delivery, Beck depression inventory was filled out and data analysis was performed by SPSS software V.16 using, chi-square and Mann-Whitney test. Results: Results showed that 13% of all participants 12.7% of the cases in normal and 13.3% in cesarean groups had postpartum depression. The severity of depression was higher in women with cesarean delivery compared to normal delivery and this difference was significant (mean rank 172.29 vs. 128.71, p<0.0001). There was no significant difference in the level of depression between two groups according to their age, job, parity, baby's sex, marital satisfaction and wanted/unwanted pregnancy. Conclusion: The prevalence of postpartum depression was higher in women with caesarian delivery compared to women with normal delivery